Revealing the Environmental Ideology behind Anti-Nuclear Discourse in Japan Post Fukushima 3.11 - Amanullah, Moh Gandhi; Faruk; Budi Irawanto (WILAYAH: The International Journal of East Asian Studies, 2025)
Anti-nuclear discourse in Japan gained a momentum after the Fukushima nuclear power plant accident in 2011. The impact of nuclear on the environment is one of the issues widely concerned in the anti-nuclear discourse. However, the ideological orientation of environmental perspectives within Japan’s anti-nuclear discourse remains underexplored. This study aims to examine environmental ideology embedded in anti-nuclear discourse by analyzing articles from Hangenpatsu Shinbun, an alternative anti-nuclear newspaper in Japan by using critical discourse analysis. The theoretical framework used as a lens to guide the research is the environmental ideology theorized by Julia Corbett. The findings reveal that the environmental ideology of anti-nuclear discourse in the media is predominantly anthropocentric and conservationist, with limited representation of ecocentric or ecological ideologies. This anthropocentric bias suggests that the discourse prioritizes human interest, often subordinating environmental concerns. Such a perspective bias perpetuating environmental policies that fail to address long-term sustainability. To mitigate this limitation, anti-nuclear discourse in Japan should adopt a more ecocentric approach, such as deep ecology. This shift would recognize the intrinsic value of nature and promotes a holistic, sustainable relationship between humans and ecosystems, contributing to the development of more balanced environmental policies for the future.